2015
DOI: 10.1002/jcp.25272
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nandrolone Stimulation on Testosterone Biosynthesis in Leydig Cells

Abstract: Anabolic androgenic steroids (AAS) are among the drugs most used by athletes for improving physical performance, as well as for aesthetic purposes. A number of papers have showed the side effects of AAS in different organs and tissues. For example, AAS are known to suppress gonadotropin‐releasing hormone, luteinizing hormone, and follicle‐stimulating hormone. This study investigates the effects of nandrolone on testosterone biosynthesis in Leydig cells using various methods, including mass spectrometry, wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 37 publications
3
36
0
Order By: Relevance
“…Furthermore, the expression of positive and negative regulators of cell proliferation such as Cyclin D1, Cyclin E, Cdk1/2 and p21, p53 resulted to be down-and up-regulated respectively, further confirming a strong repression of cell proliferation induced by nandrolone in HepG2 cells. An inhibitory effect on cell growth exerted by nandrolone has been already reported on other cell lines such as the Leydig cells 2,33 .…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, the expression of positive and negative regulators of cell proliferation such as Cyclin D1, Cyclin E, Cdk1/2 and p21, p53 resulted to be down-and up-regulated respectively, further confirming a strong repression of cell proliferation induced by nandrolone in HepG2 cells. An inhibitory effect on cell growth exerted by nandrolone has been already reported on other cell lines such as the Leydig cells 2,33 .…”
Section: Discussionmentioning
confidence: 60%
“…In a previous study, we demonstrated that ND treatment of Leydig cells interferes with the biosynthesis of testosterone in a dose increase-dependent fashion [13]. As a consequence of the results obtained in vitro, here an animal model was utilized to better understand the side effects of ND administration in sedentary and trained mice.…”
Section: Discussionmentioning
confidence: 91%
“…As previously described, the equine estrogens are often contained in the HRT preparations: comparing the metabolites of equine estrogens with the human, a greater potential for causing oxidative damage was described (Zhang et al, 1999 ; Tibullo et al, 2013 ; Pomara et al, 2016 ). A metabolite of equine estrogen, 4-hydroxyequilenin, has been shown to cause oxidative damage and single-strand breaks in λ phage DNA (Chen et al, 1998 ) and in breast cancer cell lines, especially ER-positive cell lines (Liu et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%